Whole school evaluation as imperative for total quality management in school evaluation programme (2010)
The paper examined the imperatives of Total Quality Management (TQM) in school evaluation in Nigerian schools using the whole School Evaluation(WSE) approach. It observed that evaluation is central to achieving excellence in the education system, which largely depends on the quality measures applied. Quality was presented as an essential ingredient of achieving excellence, efficiency and effectiveness of a nation's education system. TQM, a panacea found in the Asian and Western world to be effective in improving any ailing education system was posited as a veritable tool for driving the existing evaluation framework in the country to accomodate the new concept of Whole School Evaluation. TQM, a comprhensive approach to school management required that all components of an organisation or programme work efficiently according to laid down specification of standards. Four imperatives: morals, environmental, survival and accountability were germane in the application of TQM in the evaluation process in our schools. WSE approach to evaluation holds true the principles of TQM. WSE process, a framework usually backed up by national policy, examined nine functional areas and was executed by the school prior to the commencement of the on-site evaluation by accredited external body. The approach had the capacity to incorporate all stakeholders ranging from the school management team, the governing board, parents, students, teachers, community, to ministry officials. The paper contended that WSE be introduced into the education system in view of its numerous benefits and quest for provision of quality and sustainable education in Nigeria.